Improving Network Lifetime In MANET Using VGDRA - Kaur, Gagandeep; Singh, Gurbahar (International Journal For Research In Advanced Computer Science And Engineering, 2016)
A virtual grid based dynamic routes adjustment scheme for mobile sink based wireless sensor networks was introduced in recent times. Routing is defined as moving of information from source to destination. As in virtual gridding protocol, the cluster head was chose once the communication started due to this after the energy of the node is consumed the communication stopped thereby decreasing the network life time. So in this proposed work the cluster head is selected after energy of the current cluster head is utilized, in this case a threshold value is set. The problem of straight line communication is also considered, as the sink is kept mobile the nodes that are far away from the sink consume more energy and time for communication process as the distance between the sink and node is quite large so to resolve the problem a rechargeable node employed at the centre of the grid. This node is used for the direct straight line communication with the sink thus consuming the less amount of energy as these are rechargeable nodes. By using this routing concept, the energy of the system will be decreased that will result in increasing the life time and the stability of the network. Therefore this method of routing is considered to be better and more efficient than the traditional algorithm of routing.